Study of the Impact of Dzun Nuun Prayer on Brain Wave Patterns of Adolescents with Overthinking Symptoms Through Electroencephalography (EEG) Examination - Putri Zulfikah; Heni Sumarti; Istikomah (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
Overthinking is a psychological disorder characterized by excessive, repetitive thoughts. The Dzun Nuun prayer is believed to be a spiritual approach capable of calming the mind and can be examined through the activity of alpha and beta brain waves. This study aims to determine the normalized intensities of alpha and beta waves before and after the administration of the Dzun Nuun prayer stimulus, and to assess its effect on overthinking among adolescents. The research employed a quantitative, experimental method using an Electroencephalography (EEG) device. The subjects were 20 final-year university students experiencing overthinking, and the data were analyzed using a Paired-Samples T-Test. The results showed increased intensities of alpha waves (0.05–0.30) and beta waves (0.01–0.13) following the Dzun Nuun prayer stimulus. Statistical testing revealed significant effects on both alpha (p = 0.026) and beta waves (p = 0.039), indicating a meaningful influence. In conclusion, the Dzun Nuun prayer has a positive effect on brain activity, reducing overthinking symptoms by enhancing relaxation and focus-related brain waves.